Sejarah Peradaban Islam: Telaah Pada Fase Dinasti Turki Usmani, Safawiyah, Dan Muqal - Mahfudah, Rifkatul; Rizal, Muh.; Sulaiman, Umar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study examines the history of Islamic civilization through the analysis of the power phases of three major empires: the Ottoman Sultanate, the Safavid Dynasty, and the Mughal Empire. The method used is library research, which utilizes sources such as books, journals, and historical documents to obtain data on the political structure, governance system, economy, society, and culture of these three empires. The results of the study indicate that the Ottoman Sultanate, the Safavid Dynasty, and the Mughal Empire had significant periods in the development and spread of Islam worldwide, highlighting various aspects such as politics, society, economy, and culture. For instance, the Ottoman Sultanate was known for its efficient governance system and vast territorial reach, while the Safavid Dynasty introduced profound Shia political policies and influenced Persian culture. Meanwhile, the Mughal Empire, although shorter-lived, made significant contributions to the development of Islam in Central Asia.